75.7k views
1 vote
Is 5 a solution to the equation 3(x+1)=7(x-2)-3

User Gaf King
by
5.9k points

2 Answers

7 votes

Answer:

yes

Explanation:

3x5=15

3x1=3 15+3=18

7x5=35

7x2=14 35-14=21 21-3=18

18=18

User Shabeer
by
6.7k points
4 votes

Proof:

Given
3(x+1)=7(x-2)-3

To prove that the solution of
3(x+1)=7(x-2)-3 is 5,


3(x+1)=7(x-2)-3

On taking off the brackets we get,


3x+3=7x-14-3

On grouping the x terms together,


7x-3x=14+3+3

On solving we get,


4x=20


x=(20)/(4)

On dividing 20 by 4,


x=5


\Rightarrow Hence proved that the solution for
\bold3(x+1)=7(x-2)-3\bold is 5.

User Jimtut
by
5.6k points